We can re-create the quadratic equation by
(x -3) * (x -2)
x^2 -5x + 6 = 0
Use pythagorean theorem for all of them
a. 3, 4, 5
3^2+4^2?5^2
9+16?25
25=25
right
b. 5, 6, 7
5^2+6^2=7^2
25+36=49
61>49
acute
c. 64+81=144
145>144
acute
hope this helps!
Answer:
x = y = -2
Step-by-step explanation:
Hope this helps
The length of that arc is (90/360)·2·π·6 = (1/4)·12·π = 3·π ≈ 9.42 units;
Answer:
1. x^2-9x+18
2. 2x^2-4x-16
3. 3x^2-19x-14
4. 6x^2 +14x + 8
Step-by-step explanation:
1. (x-3)(x-6)
x^2 - 6x - 3x +18 = x^2-9x+18
2. (2x+4)(x-4)
2x^2-8x+4x-16 = 2x^2-4x-16
3. (x-7)(3x+2)
3x^2+2x-21x-14 = 3x^2-19x-14
4. (3x+4)(2x+2)
6x^2+6x+8x+8 = 6x^2 +14x + 8